A Study on the Existence of the Lajher Pandhalungan Dance in Situbondo Regency East Java - Dwi Imanda , Fatvil; Wisnu Pamenang, Nandhang; Lestianto Utomo Putro, Renaldi (Universitas Negeri Semarang, 2025)
This study analyzes Lajher Pandhalungan Dance, or popularly called Landhung Dance, as a cultural icon of Situbondo Regency in the Horseshoe region, north coast of Java. This dance was developed by the late Regent H. Dadang Wigiarto, SH, and developed by the Situbondo Arts Council. Choreographically, Lajher Pandhalungan Dance is divided into three levels (Landhung Cengker, Landhung Anom, and Landhung) with a complex movement structure, including 5 types of head movements, 16 hand movements, 4 body movements, and 2 foot movements. This flexibility allows the dances to be performed solo or in groups by dancers of various age groups. The dance theme fundamentally represents the socio-economic identity of the Situbondo community, especially the professions of fishermen and farmers, as well as the Pandhalungan cultural identity which is an acculturation between Javanese and Madurese ethnicities. The existence of Lajher Pandhalungan Dance is supported by two main factors: internal and external. Internal factors include the artistic creativity of the dance group and its inherent choreographic elements. Meanwhile, external factors include audience enthusiasm and promotional strategies through social media. The dance is consistently performed, including as the opening dance at the Situbondo Ethnic Festival 2023, and has been integrated into the compulsory extracurricular curriculum for elementary to junior high school students, demonstrating systematic efforts in cultural preservation and regeneration.